(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
For forest tree species analyzed their intrapopulation structure, which was based on analysis of the ecosystem status of different groups of plants. It is shown that the formation of distinct intrapopulation structural groups (cohorts) is one of the consequences of general biological features characteristic of these plant life forms. Cohorts were formed of plants from a number of different characteristics (age, size, vitality etc.). It is an objective basis for a range of methods tested in the studying of population as a whole, for the studying of structural intrapopulation groups. The theoretical analysis of the intrapopulation structure problem of forest-forming tree species was supplemented by its consideration on the example of Acer platanoides.